Regulacje służące ochronie genius loci jako spoiwa łączącego dziedzictwo materialne i niematerialne - Lena Gryz (Studia Administracyjne)
The recognition of genius loci has been acknowledged by international organizations, primarily ICOMOS, whereas Polish legislation does not adequately address this concept. The spirit of place serves as the nexus between tangible and intangible heritage, and without its consideration, the holistic approach to heritage preservation cannot be effectively pursued. Consequently, there is a pressing need for regulations specifically focused on safeguarding the genius loci. This publication aims to trace historical and substantive changes in defining the spirit of place, conduct analyses of international legal acts and doctrinal documents forming the basis of the genius loci protection system, identify deficiencies in the Polish legal framework, explore possibilities for utilizing existing regulations in preserving the spirit of place, and present proposals for substantive and legislative changes in the field of genius loci protection. In both international and Polish law, numerous acts and documents can be leveraged for protecting genius loci, notably: Quebec Declaration on the Preservation of the Spirit of Place, Convention Concerning the Protection of the World Cultural and Natural Heritage, Convention for the Safeguarding of the Intangible Cultural Heritage, the Nature Conservation Act and the Spatial Planning and Development Act. Nevertheless, dedicated provisions for protecting the spirit of place are essential, including the introduction of mandatory studies and methods for its preservation in local spatial development plans, municipal development strategies, heritage conservation programs and cultural park protection plans. Additionally, regulations safeguarding the view from and to heritage sites should be instituted. While few Polish bylaws already touch upon the protection of genius loci, its consideration by decision-makers remains voluntary. To enhance the effectiveness of preserving the spirit of place, attention must be drawn to the necessity of maintaining and fostering this phenomenon as a link between tangible and intangible heritage. This study employs a formal-dogmatic and retrogressive methodology.